ALIH KODE PENYIAR RADIO OZ 94,4 FM BANDARLAMPUNG DAN IMPLIKASINYA TERHADAP PEMBELAJARAN BAHASA INDONESIA DI SMA - asih kurniawati; wini tarmini; kahfie nazaruddin (Jurnal Kata (Bahasa, Sastra, dan Pembelajarannya), 2013)
This research discusses about code switching Oz Radio announcer 94,4 FM and the implication of  Indonesian Language teaching in high school. The goal of this research is to describe the forms and the cause of code switching Oz Radio announcer 94,4 FM and the implication if Indonesian Language in high school. The result of the research shows that the code switching phenomena is found for about 161. There are there kind of code switching they are tag switching, intrasentential switching, and intersentential switching. Tag switching is caused by the changing of the situation, influenced by interlocutor, and topic changing. Intrasentential switching is caused by quoting someone’s conversation, topic changing, wants to be assume as a “well-educated person”, influenced by interlocutors that translate it to English, and avoid from the impolite words in Indonesian Language, whereas intersentential switching is caused by quoting someone’s conversations, the changing of the media, wants to be assumed as a “well-educated person”, influenced by the interlocutors that changes to English, topic changing and the third person. Based on the research, code switching can be used as a teaching source for Indonesian Language that gives many benefits, knowledge and the application to the students about the variation usage or language variation that occur by context, so it can make a communicative communication. Keywords: code switching, Oz Radio announcer 94,4 FM